Synthesis, insecticidal activities and resistance in Aedes albopictus and cytotoxicity of novel dihaloacetylated heterocyclic pyrethroids. Issue 2 (27th August 2019) - Zhu, Qiuyan; Yang, Yang; Lao, Zhiting; Zhong, Yingying; Zhang, Bingjie; Cui, Xiping; O'Neill, Paul; Hong, David; Zhang, Kun; Zhao, Suqing
Abstract: BACKGROUND: The use of safe and effective insecticides against mosquito‐borne stocks is still one of the most effective ways to rapidly interrupt the spread of diseases such as malaria, dengue etc., but many insects are resistant to most insecticides and most of the traditional pyrethroids (like permethrin, deltamethrin etc.) contain phenoxy groups so it is easy to form dibenzofuran, a pollutant, after photodegradation. It is therefore necessary to synthesize novel pyrethroids which have better mosquito‐killing activity, poor resistance to mosquitoes, and no dibenzofuran formation during photodegradation. RESULTS: A series of novel dihaloacetylated heterocyclic pyrethroids were synthesized to enhance antimosquito activity. Bioassays based on the guidelines of the Chinese Center for Disease Control and Prevention (CDC) indicate that the synthesized compounds DCA‐O (LC50 = 2.95 ± 0.05 μg L −1 ), DCA‐01 (LC50 = 5.83 ± 0.36 μg L −1 ) and DCA‐11 (LC50 = 5.79 ± 1.51 μg L −1 ) exhibit high insecticidal activities and sensitivity against Aedes albopictus while deltamethrin and permethrin produced moderate levels of resistance. Moreover, the analysis of the photodegradation implies that the novel compounds synthesized by substituting a phenoxy group with a heterocyclic ring do not form dibenzofuran, a pollutant. Lastly, the cytotoxicity data of pyrethroids on human dopaminergic neuroblastoma SH‐SY5Y cells confirm that the synthesized compounds have low toxicity for the cells. CONCLUSION: Novel dihaloacetylated heterocyclic pyrethroids, made by simple synthesis steps, have better antimosquito activity, lower drug resistance, are less polluting to the environment and show low toxicity to human nerve cells. This also provides an effective idea for the synthesis of pyrethroids. Novel dihaloacetylated heterocyclic pyrethroids have better antimosquito activity, lower drug resistance, are less polluting to the environment, ahow low toxicity to human nerve cells and simple synthesis steps. © 2019 Society of Chemical Industry Abstract : Novel dihaloacetylated heterocyclic pyrethroids have better anti‐mosquito activity, lower drug resistance, less pollution to the environment, low toxicity to human nerve cells and simple synthesis steps.